Direct Comparison of d-DNA and l-DNA Strand-Displacement Reactions in Living Mammalian Cells - Zhong, Wenrui (ACS Synth Biol, 2020)
To overcome technical challenges associated with the use of DNA strand-displacement circuits in vivo, including degradation by cellular nucleases, researchers are increasingly turning to bio-orthogonal l-DNA. Although enhanced stability and improved performance of l-DNA-based circuits within living cells is often implied, direct experimental evidence has not been provided. Herein, we directly compare the functional stability and kinetics of d-DNA and l-DNA strand-displacement in live cells for the first time. Compared to conventional d-DNA, we show that l-DNA strand-displacement reaction systems have minimal “leak”, fast reaction kinetics, and prolonged stability inside living cells. Furthermore, using “heterochiral” strand-displacement, we demonstrate that bio-stable l-DNA reaction components can be easily interfaced with native DNA inside cells. Overall, our results strongly support the broader adoption of l-DNA in the field of DNA molecular circuitry, especially for in vivo applications.